The Green Hornet - Gondry, Michel; Rogen, Seth, 1982-; Zhou, Jielun, 1979-; Waltz, Christoph, 1956- (Culver City, Calif. : Sony Pictures Home Entertainment, 2011)
After the death of his father, a rich playboy becomes the crime-fighting hero known as the Green Hornet.
Based on the radio program.
Originally released as a motion picture in 2011.
Features: "Awesoom" gag reel, filmmakers' commentary, The Black Beauty : rebirth of cool, writing "the Green Hornet."
Seth Rogen, Jay Chou, Christoph Waltz, Cameron Diaz, David Harbour.
MPAA rating: PG-13.
DVD, Dolby digital 5.1 surround.
Keywords: Superheroes -- Drama; Good and evil -- Drama; Criminals -- Drama; Action and adventure films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Fiction films; Based on the book; Feature films; Comedy films; Superhero films